221k views
2 votes
If r, s, and t are constants such that
(x^(r-2)\cdot y^(2s)\cdot z^(3t+1))/(x^(2r)\cdot y^(s-4)\cdot z^(2t-3))=xyz for all non-zero x, y, and z, then solve for
r^s\cdot t. Express your answer as a fraction.

User Farjana
by
5.7k points

1 Answer

4 votes


(x^(r-2)y^(2s)z^(3t+1))/(x^(2r)y^(s-4)z^(2t-3))=x^(-r-2)y^(s+4)z^(t+4)=xyz


\implies\begin{cases}-r-2=1\\s+4=1\\t+4=1\end{cases}\implies r=s=t=-3


\implies r^st=(-3)^(-3)(-3)=(-3)^(-2)=\frac1{(-3)^2}=\frac19

User Ricco
by
5.4k points